HIV-/AIDS-Related Knowledge and Attitudes among Saudi Health Professionals and Students: A Review Article - Nasir, Elwalid Fadul (European Journal of General Dentistry, 2025)
Human immunodeficiency virus (HIV) is an infection that attacks the immune system of the body, while acquired immunodeficiency syndrome (AIDS) is the most advanced stage of the disease. It has been reported that 9 out of every 10 cases in Saudi Arabia remain undiagnosed. All health care staff are at risk of HIV infection with the increasing numbers of HIV-positive patients.This study reviewed the literature on HIV- and AIDS-related knowledge and attitudes among Saudi health professionals and students. A literature search using combined keywords was performed in three scientific databases of peer-reviewed publications during the past 10 years (2014–2024), leaving a final selection of 19 studies included in the review.A variety of health professionals/students have been studied. Most of the studies reported major misconceptions or unsatisfactory level of knowledge, negative attitudes, and behaviors. The most commonly used sampling approach was convenience sampling.This review highlighted the importance of continuously evaluating health professionals'/students' knowledge and attitudes regarding HIV/AIDS. The recommendations by most of the studies that institutions tailor their educational approach to adopt the most efficient and effective ways of spreading HIV/AIDS awareness and increasing health workers' knowledge through in-service training might enhance their perceived confidence and thus their willingness and attitudes toward treating such patients.
Keywords: attitudes; behavior; health students; health workers; HIV/AIDS; knowledge; review; Saudi Arabia